Socialization and Practice of Processing Coconut Cooking Oil based on SNI 3741:2013 Quality Standard for Residents in Gondoruso Village, Pasirian Lumajang - Ermawati, Frida Ulfah; Dzulkiflih, Dzulkiflih; Aji, Tony Seno; Afifah, Choirul Anna Nur; Zainuddin, Abu (Lumbung Inovasi: Jurnal Pengabdian kepada Masyarakat, 2022)
Gondoruso village, Pasirian Lumajang has many coconut trees. However, the coconuts were only harvested and sold in the local market at a price of IDR 2,000-3,000/fruit. Some local residents had initiated efforts to process coconuts into cooking oil, but the resulting oil smelled rancid so they stopped it. This paper reported the results of our community service activities in assisting Gondoruso Village residents to proceed coconut into cooking oil that meets the SNI 3741:2013 quality standard. The aim was to train the residents’ skills in producing qualified coconut cooking oil so they could earn extra family income. Eight old coconuts were grated, and thick coconut milk was taken. The coconut milk was left overnight in the refrigerator to produce lumps of coconut milk. The lumps of coconut milk were taken and cooked over low heat. About 10 minutes later, the oil started to come out, and the cooking process continued for 40-45 minutes until all the oil-came out, and 550 ml of cooking oil was produced. The SNI 3741:2013 quality test revealed that the cooking oil was of very good quality because the values of 6-SNI parameters met the standard, i.e., organoleptic is liquid, clear yellow, sweet coconut, and tasteless; moisture content=0.13% w/w; acid number=0.06% w/w; peroxides number=0; the pelican oil=negative, and the linoleic acid=0.13%. The production and market analyses stated that the production cost of 550 ml of coconut oil=IDR 27,600, while the selling price in the market=IDR 80,000/500 ml.